Examining the mediating role of celebrity endorsement in green advertisements to improve the intention of Egyptian Millennials towards environmental behaviours in tourist destinations - Kamel, Noha (2020)
Celebrity-endorsed advertisements have a powerful influence, especially on young generations like millennials. At the same time, green advertising is a growing trend used by many destinations and organisations for environmental protection initiatives. Celebrity endorsement in green advertisement could be a viable solution for many marketers in tourist destinations to engage and support millennials to be eco-friendly during their travels. Hence, the purpose of this study is to investigate the mediating role of using celebrities as endorsers in green ads to influence the intention of Egyptian millennials towards environmental behaviours in tourist destinations. Descriptive analysis, Structural Equation Modelling (SEM) and Confirmatory Factor Analysis (CFA) have been carried out using SPSS and Amos to address the objectives of this study. Results show that celebrity endorsement mediates the relationship between green advertisements and the intentions of millennials to behave in a sustainable way in tourist destinations. This study makes the first attempt to provide evidence of how celebrities can be employed as a mediating variable in green advertisements to motivate Egyptian millennials to be environmentally responsible.